Evaluation of Race-Neutral Glomerular Filtration Rate Estimating Equations in an Indian Population - Ashok Kumar Yadav; Jaskiran Kaur; Prabhjot Kaur; Kajal Kamboj; Yoshinari Yasuda; Masaru Horio; Arnab Pal; Nusrat Shafiq; Nancy Sahni; Harbir Singh Kohli; Seiichi Matsuo; Vivek Kumar; et al. (Kidney International Reports)
Introduction: Glomerular filtration rate (GFR) estimation equations have not been extensively validated in the Indian population. Preliminary data showed that the widely used creatinine-based Chronic Kidney Disease Epidemiology Collaboration (CKD-EPICr) 2009 significantly overestimated GFR in Indians. Newer estimated GFR (eGFR) equations based on creatinine and cystatin C, omitting the race, have been recently proposed. We investigated the performance of race-free eGFR equations in the Indian population. Methods: Patients with chronic kidney disease (CKD) and potential kidney donors attending the outpatient clinic at the Postgraduate Institute of Medical Education and Research Chandigarh, India, were screened for enrolment. GFR was measured by urinary clearance of inulin and plasma clearance of iohexol. Performance of eGFR equations (CKD-EPICr(2021), CKD-EPICr-Cys(2021), CKD-EPICr(2009), CKD-EPICr-Cys(2012), CKD-EPICys, 2020Csy-B2M-BTP and 2020Cr-Csy-B2M-BTP, EKFCcr, EKFCcys, and EKFCcr-cys) were assessed against measured GFR (mGFR) using bias, precision, and accuracy (root mean square error [RMSE], mean absolute error [MAE] and P30 [% with eGFR within 30% of mGFR]). Results: A total of 412 subjects (55% with CKD), average age 47 ± 11 years with an equal distribution of males and females were enrolled. The mean mGFR in the study population was 54.2 ± 30.2 ml/min per 1.73 m2. The average mGFR in the potential kidney donor’s subgroup was 79.5 ± 23.2 ml/min per 1.73 m2. Bias was highest for creatinine-based eGFR equations (CKD-EPIcr(2021): −19.2 [−21.3 to −17.0] ml/min per 1.73 m2and CKD-EPIcr(2009): −17.0 [−19.1 to −15.0] ml/min per 1.73 m2). Cystatin C– (either alone or with other markers) based equations were slightly better but still did not reach P30 ≥ 80%. Conclusions: Race-neutral CKD-EPICr(2021) equation did not significantly improve performance as compared to CKD-EPICr(2009) equation. These observations emphasize the need for developing new eGFR equations for Indians and to standardize the mGFR for easy access to care providers for individualized patient care.